SDG 17 and global partnership for sustainable development: unraveling the rhetoric of collaboration - Cruz, Sofia Alexandra (Frontiers in Environmental Science, 2023)
As the 2030 SDG Agenda unfolds, a growing body of the literature from various disciplines is analyzing how sustainable development can be a process for change to achieve a dynamic equilibrium between the economic, social, and environmental dimensions. This article aims to critically examine the evolution and implementation of the UN 2030 agenda for sustainable development, with a particular focus on its collaborative approach. It discusses the SDG 17 called “Partnerships for the Goals. Strengthen the means of implementation and revitalize the global partnership for sustainable development”, devoting particular attention to how this SDG has been found in a blurred vision of collaboration. Actually, there has been much rhetoric about enhancing multi-stakeholder partnerships for sustainable development including the government, business sector, non-government organizations, academia, social partners, and civil society. However, reporting the difficulties and unmitigated success is not common. From the perspective of the theory of collaborative advantage, this paper examines the collaborative advantages and inertias of the process of collaborating and identifies important key elements to consider in SDG 17, such as power relations, trust, goal management, organizational cultures, and leadership.